Economic Effects in the System of Branches of Ukrainian economy: Assessment and Analysis of Dynamics Экономические эффекты в системе отраслей экономики Украины: оценка и анализ динамики - Dilenko Viktor A. (Bìznes Inform, 2013)
The article applies the economical-mathematical mechanism of “input-output” models for determination of various types of economic effects, which are being formed in the system of branches of the Ukrainian economy. Obtained time series of these effects are analysed and specific features of their evolution are revealed: absence of stable tendencies of dynamics, predominance of negative values of the considered effects for many branches, etc. В статье, используя экономико-математический аппарат моделей «затраты – выпуск», определены различные виды экономических эффектов, которые формируются в системе отраслей экономики Украины. Проанализированы полученные временные ряды данных эффектов и выявлены характерные особенности их эволюции: отсутствие устойчивых тенденций динамики, преобладание отрицательных значений рассматриваемых эффектов для многих отраслей и др.